RESILIENCE OF ELDERLY PRISONERS IN SERVING A CRIMINAL PERIOD IN CLASS IIA KARAWANG CORRECTIONAL INSTITUTION - Utama, Nuri Rezza; Priyatmono, Budi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the conditions and factors that influence the resilience of elderly prisoners at the Karawang Class IIA Correctional Institution while serving their sentence. Elderly prisoners face a range of challenges, including overcrowded conditions, declining physical health, and psychological distress from loss of freedom and social isolation. Overcrowding, which worsens the quality of care and increases the potential for conflict, exacerbates these problems. Elderly prisoners, who are already vulnerable to physical and mental health problems, must go through phases of grief, acceptance, and resilience. Using a qualitative narrative approach, this study explores how these prisoners endeavor to adapt and overcome their difficulties. Data was collected through interviews with elderly prisoners and Karawang Class IIA prison officers. The research identified key aspects of resilience, such as emotion regulation, impulse control, optimism, and causal analysis. Further findings highlighted the importance of knowing the factors that influence individuals to be resilient, such as self-esteem, social support, spirituality, and positive emotions, in fostering resilience in elderly prisoners. This research contributes to a deeper understanding of the factors that help in the process of enhancing resilience and the role of prison rehabilitation programs in improving the well-being of prisoners, especially elderly prisoners. Keywords: Elderly Resilience; Correctional Facility; Health in Prisons; Overcrowding